A comparison of a regional NSW obstetrics population to district, state and national statistics. Issue 3 (22nd June 2016) - Spurway, Jacqueline; Logan, Patricia; Pak, Sok Cheon; Nielsen, Sharon
Abstract: Background: In the central west NSW region, there are variations in population density, socioeconomic status and ethnicity. Aims: Compare and contrast the maternal characteristics and pregnancy outcomes of an obstetric population in central west New South Wales to district, state and national data. Materials and methods: A prospective cross‐sectional study involving 625 pregnant women who attended Orange or Bathurst public hospitals for obstetric ultrasounds. The women were 16 years and older and were greater than 16 weeks pregnant with a single fetus. Maternal characteristics and pregnancy outcomes were compared to district, state and national data. Descriptive comparisons and hypothesis testing were undertaken and P values or confidence intervals were provided where appropriate. Results: The average maternal age was 27.5 years, 24.6% of the women smoked during pregnancy, 31.7% of deliveries were by caesarean, 52.4% of live births were female, 7.8% of babies were born preterm and the mean live birthweight was 3297 g. Four per cent of the participants were indigenous. Conclusions: Analysis of a regional sample indicated differences in indigenous population distribution, maternal age and smoking when compared to broader statistics. This has local implications for education, workforce, government and public health planning.